Chuva de sementes sob árvores isoladas em pastagens próximas a fragmentos florestais - Carreira, Daiane Cristina (2013)
The semideciduous seasonal forests in the state of São Paulo are highly fragmented due to the history of intensive human interventions in the landscape, especially agricultural activities. In this context, we selected the Basin Corumbataí (BHRC), São Paulo (22 ° 04'46 "and 22 ° 41'28" S, 47 ° 26'23 "and 47 ° 56'15'' W) to understand the role of native trees isolated in pastures consolidated in maintaining connectivity between forest fragments near. So we had a goal, answer the following questions: i) Isolation of native trees in pastures, determined by distance, proximity index, fragment size and forest cover (within a radius of 900 m from the isolated tree), as well as characteristics of isolated trees, height and crown area, can determine the abundance and richness of seeds derived from the seed rain under isolated trees? ii) The richness and abundance of seeds produced from the seed rain is greater under native trees isolated in pastures than inside fragments of semideciduous forests adjacent to pastures of BHRC? We installed 36 seed collectors with an area of 1.5 m2: 18 of them within three fragments, and the other 18 under isolated trees in pastures. We collected fortnightly for six months. We recognize, identify and categorize the seeds on the type of dispersal and seed size sampled. To answer the first question, we tested whether differences in the abundance and species richness could be determined by isolation and structural characteristics (height and crown area) of native trees in the pastures of BHRC regarding forest fragments. Conducted multiple regression analyzes using generalized linear models. To reply the second question, we performed an analysis of covariance to compare the richness and mean abundance of seeds among isolated trees and inside the fragments. We use the sort method of Non-Metric Multidimensional Scaling (NMDS) to ascertain the similarity in species composition in the two environments; use the rank-abundance curve to analyze evenness in the distribution of species in both environments. Regarding isolated trees in pastures, we found that those with higher canopy cover and closer to forest fragments exhibit greater abundance of animal dispersed seeds, especially when considering the seeds zoochoric "small" (<3 mm), whose abundances were higher in trees with greater canopy cover, closer to forest fragments and in areas with high forest cover. Plenty of seeds > 3 mm, anemochoric or autochorous as well as the wealth of animal dispersed anemochoric or autochorous, no significant differences in relation to the isolation of the trees. Comparing seed rain under trees and isolated within the forest fragments, found that forest fragments are richest and most abundant species arising from the rain, but the difference was expressed only in relations: total species richness anemochoric, being clearer results for the seeds between 3.0 mm and 10 mm and larger than 10 mm; abundance anemochoric of between 3.0 mm and 10 mm and the total wealth of animal dispersed, especially those smaller than 3.0 mm. NMDS analyzes revealed that most of the samples (both trees as isolated forest fragments) share the same species. Through rank-abundance curve, we found that the evenness in the abundance of species collected is distributed differently (p = 0.03) and between individual trees within the forest fragments, being more equitable within the fragments, in addition, more species were found in the interior of the fragments under isolated trees. Isolated trees in pastures can serve as recruitment points of seeds and plants and potentially contribute to maintaining the flow of propagules, acting as connectors between forest fragments scattered across the landscape. Nevertheless, the retention and conservation of forest fragments dispersed in agricultural matrices can contribute to the maintenance of seed rain, given the composition and structure of species present.